Carotenoid stability during storage of yellow gari made from biofortified cassava or with palm oil - Bechoffa, Aurelie; Chijokeb, Ugo; Tomlins, Keith; Govindena, Pesila; Ilonac, Paul; Westbya, Andrew; Boy, Erick (Elsevier, 2015)
The carotenoid composition of gari made from biofortified cassava (BG) was compared to that of existing gari of similar appearance but made from white cassava with added red palm oil (RPG). Storage of both yellow gari products was modelled at ambient temperatures typical of tropical areas (19–40 °C) over a 3-month-period at constant relative humidity. Carotenoid content and hence vitamin A activity of the gari products decreased markedly with time and temperature. Trans-β-carotene degradation fitted well the kinetics predicted by the Arrhenius model, in particular for BG. Activation energies for trans-β-carotene were 60.4 and 81.0 kJ mol−1 for BG and RPG respectively (R2 = 0.998 and 0.997, respectively); hence the minimum energy to cause degradation of trans-β-carotene in gari was lower with BG. Rates of degradation of 9-cis-β-carotene in gari were of the same order as with trans-β-carotene. Although the initial content of trans-β-carotene was twice as high in the BG compared to RPG, trans-β-carotene in BG degraded much faster. Results showed that the average shelf life at ambient temperature for BG was significantly shorter than for RPG and therefore carotenoids in BG were less stable than in RPG.